2011
DOI: 10.1016/j.freeradbiomed.2011.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent changes in 8-oxoguanine-DNA glycosylase activity are modulated by adaptive responses to physical exercise in human skeletal muscle

Abstract: 8-Oxo-7,8 dihydroguanine (8-oxoG) accumulates in the genome over time and is believed to contribute to the development of aging characteristics of skeletal muscle and various aging-related diseases. Here, we show a significantly increased level of intrahelical 8-oxoG and 8-oxoguanine DNA glycosylase (OGG1) expression in aged human skeletal muscle compared to that of young individuals. In response to exercise, the 8-oxoG level was found to be lastingly elevated in sedentary young and old subjects, but returned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 88 publications
(81 citation statements)
references
References 57 publications
3
77
1
Order By: Relevance
“…We and others have shown that exercise increases the activity and content of SIRT1 (Hart et al 2014;Kang et al 2013;Koltai et al 2011;Marton et al 2015;Radak et al 2011;Suwa et al 2008), while aging decreases NAD levels and NAMPT concentration (Koltai et al 2010). Moreover, it has also been reported that exercise training can attenuate the age associated decline in NAD and NAMT levels in skeletal muscle of rats (Koltai et al 2012).…”
Section: Introductionmentioning
confidence: 93%
“…We and others have shown that exercise increases the activity and content of SIRT1 (Hart et al 2014;Kang et al 2013;Koltai et al 2011;Marton et al 2015;Radak et al 2011;Suwa et al 2008), while aging decreases NAD levels and NAMPT concentration (Koltai et al 2010). Moreover, it has also been reported that exercise training can attenuate the age associated decline in NAD and NAMT levels in skeletal muscle of rats (Koltai et al 2012).…”
Section: Introductionmentioning
confidence: 93%
“…This was also confirmed in our recent finding from aged human skeletal muscle (Radak et al, 2011). 85 Acetylation of OGG1 is a posttranslational activation of the incision activity of this enzyme. 14,29 Thus, it cannot be excluded that the age-associated increase in 8-oxoG levels could be due to the large decrease in acetylation of OGG1.…”
mentioning
confidence: 99%
“…OGG1 has been shown to be acetylated by p300/CBP at lysines 338 and 341, which results in a significant increase in its activity [81]. We have recently demonstrated that Ac-OGG1 is present in human skeletal muscle and rat tissues, and the level of acetylation decreases with aging, whereas a parallel pattern was found for SIRT1 activity [82,83]. Moreover, we have shown that resveratrol administration decreases the acetylation level of OGG1 and ablation of SIRT1 by siRNA-increased levels of Ac-OGG1.…”
Section: Sirtuins In Regulation Of Genome Integritymentioning
confidence: 97%